The rise in takeover premiums - Nathan, Kevin S; O'Keefe, Terrence B (Journal of Financial Economics, 1989)
Cash tender, cash merger, and stock merger takeover premiums for 1974–1985 are approximately bouble those for 1963–1973. Cash tender repurchase premiums also rose in 1974. Thse upward shifts remain after we control for the business cycle and a possible time trend in premiums. The shift in both takeover and repurchase premiums in 1973–1974 is consistent with some event not unique to the takeover market affecting the capital markets in 1973–1974. We also investigate the possible effect on takeover premiums of the 1986 Williams Act and conclude that it does not explain the premium increase.